Unlocking the Potential: Exploring Factors and Overcoming Challenges in Gamifying English Literacy - Kurniawan Suryatama; Ika Lestari Damayanti (UNIB Press, 2023)
Gamification in the education system emerges for the first time in the late 2000s, and since its emergence, gamification has gained recognition as an innovative approach in education, creating dynamic and engaging learning environments. However, with its current emergence, studies relating to gamification in education are still limited. As such, the current study is conducted to answer two research questions. First, what factors to be considered when applying gamification into the teaching process, and second, what are the challenges when applying gamification into the teaching process. This research used interview to collect the data from two English teachers who have been implementing gamification in their teaching for several time, and thus the present study falls into qualitative research. The findings emphasize the importance of considering game mechanics, engagement and motivation levels, alignment with learning outcomes, learner needs and preferences, and contextual factors to effectively implement gamification. Additionally, the study highlights challenges such as designing effective game mechanics, potential distraction from learning goals, balancing gamification with traditional teaching methods, and ensuring sufficient resources and support for implementation. These findings underscore the necessity for teachers to comprehend gamification and evaluate its compatibility with students' learning needs in order to achieve better educational outcomes.